The diversity of parasitoid wasps in Tamaulipas: Ichneumonidae family - Ruiz-Cancino, Enrique (Universidad Autónoma de Tamaulipas, 2011)
This article reports the ichneumonid collected in the state of Tamaulipas from 1981 to 2011, and the list of new species described in the Insect Museum of the Facultad de Ingeniería y Ciencias de la Universidad Autónoma de Tamaulipas during the period 2000-2011.